Fundamentals of organizational behavior - Dubrin, Andrew J. (Singapore, 2009)
Welcome to the fourth and slightly expanded edition of Fundamentals of Organiza-tional Behavior. This book is designed for courses in organizational behavior and management that focus on the application of organizational behavior knowledge to achieve enhanced productivity and satisfaction in the workplace.